The Effect of Deferred Tax Expenses, Profitability and Leverage on Earnings Management: Pengaruh Beban Pajak Tangguhan, Profitabilitas dan Leverage terhadap Manajemen Laba - Rita Sriwahyuni; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2020)
This research uses quantitative research methods. The data source obtained is secondary data obtained from the Indonesia Stock Exchange (BEI). The data will be analyzed using the classical assumption test method, the goodnes of fit model test and multiple linear regression. The independent variables in this study are dependent tax expense, profitability and leverage. The dependent variable in this study is earnings management.Based on the data analysis conducted, it is concluded that deferred tax expense and profitability have no effect on earnings management. This means that earnings management cannot be measured by the variable deferred tax expense and profitability. However, the leverage variable has an effect on earnings management. This means that the leverage of a company can be used as a guide in determining earnings management